Tempeh as a Cultural Heritage in Indonesia: Intergenerational Perception - Anwar, Khoirul; Maskar, Dadi H.; Prasetyo, Irene Nuariza; Kusumawati, Intan (Jurnal Gizi dan Pangan, 2023)
This study aimed to assess how people perceive tempeh. The study was conducted using an online self-administered questionnaire among 340 respondents aged between 11 and 58 years. The results showed that respondents perceived tempeh as an Indonesian cultural food (97.70%), a highly nutritious food (99.41%), and a superfood (86.47%), and 51.76% of respondents consumed 50 g of tempeh daily. Most respondents perceived tempeh to have economic impact (91.7%) and used it as a food for celebrations (95.29%), and there was no significant differences between generations (p<0.05). The conclusion is that tempeh is perceived as an Indonesian cultural food that has cultural, economic, and nutritional value.